SISTEM INFORMASI PENGIRIMAN BARANG DI PT FADILLINDO JASA ANTARAN BERBASIS WEB - Maulana, Faris; Rachmawati, Fitria (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
Recapitulation of recording documents is carried out when recording when goods are entered, and when goods are out (delivery of goods). Every month a document recapitulation is carried out to control the timeliness and delay in the delivery of documents or goods, who is responsible for controlling incoming or outgoing goods is an admin. In this process, an admin will sort the goods to be sent to various regions, usually an admin can find out if it was sent or not when the courier returns to the office. Making this system aims to control the courier in the delivery of the goods they carry. So that when there is an urgent item, the delivery can be monitored. The research method used is the waterfall. Based on the analysis, design, results and discussion in previous chapters, conclusions can be drawn, namely: (1) The system built can at least facilitate the employees of PT.Fadillindo Jasa Antar, in managing goods delivery services and can provide information to customers quickly and accurate. (2) With this web-based delivery application, it is easier for employees to manage data, customers can also come directly to the delivery service to send goods and an application is available to serve customers when they want to make transactions on the spot. (3) The application for delivery of goods also makes it easier for couriers to process transactions, so that couriers do not have to bother recording every transaction made with customers manually or by hand.